Investigation of therapeutic effects in the wound healing of chitosan/pGM-CSF complexes - ÖZBAŞ, SUNA (My University, 2022)
Granulocyte macrophage colony-stimulating factor (GM-CSF) has been shown to promote the growth, proliferation, and migration of endothelial and keratinocyte cells. Chitosan has been widely used as a biopolymer in wound-healing studies. The aim of this study was to investigate the in vitro proliferative effects of chitosan/pGM-CSF complexes as well as the therapeutic role of the complexes in an in vivo rat wound model. The effect of complexes on cell proliferation and migration was examined. Wounds were made in Wistar-albino rats, and examined histopathologically. The cell proliferation and migration were increased weight ratio- and time-dependently in HaCaT and NIH-3T3 cell lines. Wound healing was significantly accelerated in rats treated with the complexes. These results showed that the delivery of pGM-CSF using chitosan complexes could play an accelerating role in the cell proliferation, migration, and wound-healing process.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Wound healing; Chitosan; pGM-CSF; Complexes; COLONY-STIMULATING FACTOR; MOLECULAR-WEIGHT; GROWTH-FACTORS; GENE; NANOPARTICLES; DELIVERY; PROLIFERATION; POLYPLEXES; EFFICIENCY; CYTOKINES; Wound healing; Chitosan; pGM-CSF; Complexes